2018
DOI: 10.1364/oe.26.002410
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved measurement of optical radiation-pressure forces with optical coherence tomography

Abstract: A weakly focused laser beam can exert sufficient radiation pressure to manipulate microscopic particles over a large depth range. However, depth-resolved continuous measurement of radiation-pressure force profiles over an extended range about the focal plane has not been demonstrated despite decades of research on optical manipulation. Here, we present a method for continuous measurement of axial radiation-pressure forces from a weakly focused beam on polystyrene micro-beads suspended in viscous fluids over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Second, we assumed that the mechanical response of the 0.1-μm beads was negligible. This assumption was supported by both theoretical predictions and experimental observation of F rad 44 , and experimental observation of OCT scattering intensity (Supplementary Methods). Third, we assumed that the photothermal response in our single-concentration samples was transversely uniform within the volume considered for photothermal fitting.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Second, we assumed that the mechanical response of the 0.1-μm beads was negligible. This assumption was supported by both theoretical predictions and experimental observation of F rad 44 , and experimental observation of OCT scattering intensity (Supplementary Methods). Third, we assumed that the photothermal response in our single-concentration samples was transversely uniform within the volume considered for photothermal fitting.…”
Section: Resultssupporting
confidence: 64%
“…In this case, PF-OCE offers over 60× improvement in volumetric throughput over the current state-of-the-art OT-based microrheology techniques. Future studies will also address quantitative reconstruction of the local complex shear modulus from the measured PF-OCE bead mechanical responses by utilizing OCT-based depth-resolved measurement of radiation-pressure force 44 . Additionally, such studies may warrant bead sizes smaller than the 3-µm ones used here; the NA of the PF forcing beam could be appropriately increased to optimize forces and the corresponding displacements (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using optical coherence tomography (OCT) to monitor the dynamics of accelerated beads in real-time, we recently performed the 'OCT-version' of Ashkin's seminal experiment and measured depth-resolved radiation-pressure force profile from a low-NA Gaussian beam on polystyrene micro-beads in various viscous fluids [15]. We found that radiation-pressure force on the order of 0.1 pN/mW could be achieved depending on the characteristics of the forcing beam as well as the properties of the beads and the medium.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we combined our PF-OCE approach [16] with depth-resolved radiationpressure force measurement [15] to quantitatively reconstruct microscopic complex shear modulus around each probed bead in polyacrylamide (PAM) gels, and compare our quantitative PF-OCE results to shear rheometry. In order to obtain reliable measurements of bead mechanical response for quantitative PF-OCE, we analyzed measurement noise at key processing steps and identified data exclusion criteria based on three noise-related parameters.…”
Section: Introductionmentioning
confidence: 99%